Neonatal Resuscitation and Adaptation Score vs Apgar: newborn assessment and predictive ability. (November 2018) - Witcher, Teresa; Jurdi, Shadi; Kumar, Vidhya; Gupta, Aditi; Moores, Russell; Khoury, Joseph; Rozycki, Henry
Abstract Objective To test the non-inferiority of an alternative to the Apgar score. Study design The Neonatal Resuscitation and Adaptation Score (NRAS) was recorded in parallel to the Apgar score by a resuscitation team at deliveries. Correlation between the systems was assessed, as well as the predictive ability of NRAS and Apgar scores for mortality or short-term morbidities. Results A total of 340 infants were in the study group. The two scores correlated strongly (r  = 0.87 and 0.83 at 1 and 5 min, respectively). Those needing ventilation at 48 h of life had a 5-min NRAS < 7 in 23/26 vs Apgar < 7 (23/36, p  = 0.001). A low (0–3) 1-min NRAS score was more predictive of death, 53% vs 17%, p  = 0.0065. Conclusions NRAS correlates with Apgar status assessment, and identifies newborns who die or may require further care better than the Apgar score.